Modeling the interaction among the Ukrainian and foreign stock markets - Lyashenko, S.V. (Економічний вісник Донбасу, 2010)
The interaction between Ukrainian stock market PFTS index, Russian stock market MICEX index, and Dow Jones (the United States of America) in the shortand long-term horizon was investigated in the study. Key words: stock market, indices, regression, vector autoregression, return. У статті розглянуто взаємодію між українським індексом фондового ринку ПФТС, російським індексом ММВБ і Dow Jones (Сполучені Штати Америки) в коротко-та довгостроковій перспективі. Ключові слова: фондовий ринок, індекси, регресія, векторна авторегресія, дохідність. В статье рассмотрено взаимодействие между украинским индексом фондового рынка ПФТС, российским индексом ММВБ и Dow Jones (США) в кратко-и долгосрочной перспективе. Ключевые слова: фондовый рынок, индексы, регрессия, векторная авторегрессия, доходность.